Collaboration or a systemic gap? Relations between oncology coordinators and representatives of patient support institutions - Aleksandra Kita (Annales Academiae Medicae Silesiensis)
Introduction: Despite the reforms being implemented in the Polish health system, the situation of oncology patients remains difficult. The health system is unable to meet the challenges on its own, which generates the potential for cooperation with other sectors. Coordinators can serve as a link between hospitals and other patient-oriented institutions. Material and methods: The aim of the article is to assess the degree of cooperation between coordinators and representatives of social, rehabilitation, palliative care and non-governmental organizations (NGOs). The article is based on selected results of the project: “Oncological patient coordinators. Profile, experiences and opinions of persons performing the functions of coordinators in Polish hospitals”, the results of which will be described in the emerging dissertation of the author of the article. The survey was conducted in 2023. It involved 149 coordinators from Polish hospitals implementing rapid oncology therapy (szybka terapia onkologiczna – STO). The study used a survey questionnaire and individual in-depth interviews (IDI). The program IBM SPSS Statistics (29.0.0.0) was used as the main statistical analysis tool. Results: The results indicate that cooperation between coordinators and representatives of the above-mentioned institutions is marginal; 77.9% of coordinators had never cooperated with NGOs and 62.4% had no contact with social assistance. Only 12.1% frequently collaborate with palliative care, and 7.4% with rehabilitation specialists. The review also took into account oncology Unit structures used in hospitals and participation in the pilot project of the National Cancer Network (NCN; Krajowa Sieć Onkologiczna – KSO). The lack of differences in inter-institutional cooperation suggests that even in more organized models, mechanisms for coordinators to cooperate with representatives of social welfare, rehabilitation, palliative care and NGOs have not been put in place. Conclusions: There is a lack of systemic action and cooperation between coordinators and representatives of institutions that can support oncology patients. Strengthening intersectoral relationships can benefit patients and ease the burden on medical staff by implementing shared care.